William Zorach papers - Zorach, William, 1889-1966.; Zorach, William, 1889-1966.
Correspondence, speeches, lectures, writings, subject files, financial records, newspaper clippings, printed matter, sketches, and other papers relating principally to the creation, production, and sale of sculpture and paintings by Zorach and his fellow artists. Also documents Zorach's work for the Art Students League, New York, N.Y. Subjects include abstract art, aesthetics, and art instruction for children. Includes correspondence of Zorach family members including Marguerite Zorach, a transcript of Zorach's oral history interview for the Columbia University Oral History Program, and drafts of his autobiography, Art Is My Life (1967). Also includes material relating to Zorach's estate; his art dealer, Edith Gregor Halpert; and the art of Marguerite Zorach. Correspondents include Alfred Hamilton Barr, Jerry Bywaters, Lamar Dodd, Winslow Eaves, Sir Jacob Epstein, Kenneth Franzheim, Lloyd Goodrich, Edith Gregor Halpert, Max Weber, the Rockefeller family, Ellerbe and Company, and Murphy & Mackey.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Artist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barr, Alfred H., -- Jr., -- 1902-1981 -- Correspondence; Bywaters, Jerry -- Correspondence; Dodd, Lamar -- Correspondence; Eaves, Winslow, -- 1922- -- Correspondence; Epstein, Jacob, -- 1880-1959 -- Correspondence; Franzheim, Kenneth, -- 1890-1959 -- Correspondence; Goodrich, Lloyd, -- 1897- -- Correspondence; Halpert, Edith Gregor, -- 1900-1970.; Halpert, Edith Gregor, -- 1900-1970 -- Correspondence; Weber, Max, -- 1881-1961 -- Correspondence; Zorach, Marguerite, -- 1889-1966.; Zorach, Marguerite, -- 1889-1966 -- Correspondence; Rockefeller family -- Correspondence; Art Students League (New York, N.Y.); Columbia University. -- Oral History Research Office; Ellerbe and Company -- Correspondence; Murphy & Mackey -- Correspondence; Aesthetics; Art; Art -- Study and teaching; Art, Abstract; Painting, American; Sculpture, American; Zorach family -- Correspondence; Artists